Impact of Climate Change on Livelihoods: Adaptations Measures of Chepang Community - Sapkota, Bhaba Datta (NUTA Journal, 2018)
This paper analyzes impacts of climate change on livelihoods of Chepang community and their adaptation measures. The objective of this article is to assess adaptation measures practiced by Chepang community. To accomplish the desire objectives both primary and secondary data are used thoroughly. Primary data is collected via different tools of data collection such as questionnaire, observation, interview and so on. Secondary data are collected through document study. Shortages of raw materials, low agriculture productivity, shortage of spring water etc. are found as the major impacts of climate change in the study area. The data shows that cultivation is highly affected by the pattern of climate change. Series of local adaptation measures are being carried out in the sector of agriculture, water and forests, which are more traditional in approach and based on local level knowledge. The adaptation practices applied by the locals are more traditional approaches whereas some approaches are based on the support of different governmental and non-governmental programs.